Liquid and pressure-sensitive adhesives based on cassava starch and gelatin capsule residue: green alternatives for the packaging industry - Monroy, Yuliana (2023)
Natural polymer-based adhesives are green alternatives, necessary to reduce the problems impacted by synthetic adhesives. Starch and gelatin have extraordinary potential for the synthesis of biobased adhesives. Citric acid (CA), a natural acid, induces the crosslinking and hydrolyzing of both gelatin and starch. In this sense, this work deals with the use of gelatin capsule residues as a promising material to produce biobased adhesives in combination with cassava starch in the presence of different CA concentrations characterizing their mechanical, physicochemical and microstructural properties. Depending on CA concentration, formulations adjusted to different applications can be obtained such as liquid and pressure-sensitive adhesive films. The inclusion of CA allows us not only to improve the applicability of the system since it modifies the flowability of the adhesives as evidenced by the observed changes in the viscosity (from 158.3 to 90.3 for formulations with 20 and 80% CA, respectively). In addition, mechanical profiles showed that the inclusion of CA increased the adhesive bond strength (from 2230.7 to 2638.7 for formulations with 20 and 80% CA, respectively). Structural modifications induced by CA in adhesive formulations were highlighted by ATR-FTIR analysis.